Carbon dioxide transport via pipelines: A systematic review. (1st September 2020) - Lu, Hongfang; Ma, Xin; Huang, Kun; Fu, Lingdi; Azimi, Mohammadamin
Abstract: Carbon dioxide transport plays a crucial role in carbon capture and storage systems. As an economical and convenient carrier, pipelines have huge advantages in the transport of carbon dioxide. In this paper, the development of carbon dioxide transport via pipeline is systematically reviewed from four aspects: pipeline design, process, risk and safety, standard and specification. The results reveal that there are many similarities between the carbon dioxide pipeline and the natural gas pipeline, but due to different gas compositions and transportation destinations, the transport process, design, and construction considerations are quite different. Especially in terms of management, the specifications and standards for carbon dioxide pipelines are still minimal, the techno-economic framework and integrity management system are still immature. In addition, this paper summaries the challenges and future directions of carbon dioxide transport via pipeline. It is concluded that the studies on the influence of impurities on phase equilibrium and corrosion mechanisms in carbon dioxide pipeline are challenges, and the new construction and detection technologies are also crucial. With the rapid development of computer science, some interdisciplinary applications such as artificial intelligence and digital twin will promote the development of carbon dioxide pipeline. Highlights: The progress of carbon dioxide pipeline technology is reviewed. Review from four aspects: process, design, safety and specification. The technical challenges and development direction are summarized.